The Impact of AI-Powered Writing Assistants on Efl Students' Writing Anxiety and Syntactic Complexity - Helga Ferdilla; Metha Arisandi (Jurnal Pendidikan dan Sastra Inggris, 2026)
This quasi-experimental study investigated the impact of artificial intelligence-based writing assistants (Grammarly and QuillBot) on writing anxiety and syntactic complexity in Indonesian EFL students. Sixty-four undergraduate English Education students at a state university in East Java were divided into two groups: an experimental group (n = 32), which integrated an AI-based writing assistant into their essay writing process for 12 weeks, and a control group (n = 32), which received conventional writing instruction. Writing anxiety was measured using the Second Language Writing Anxiety Inventory (SLWAI) developed by Cheng (2004), while syntactic complexity was assessed through five indices using the L2 Syntactic Complexity Analyzer (L2SCA). Results of paired-samples t-tests and independent-samples t-tests indicated that the experimental group experienced a statistically significant reduction in writing anxiety (t = 4.83, p < 0.001, d = 0.87), with the largest reduction in the cognitive anxiety subscale. Additionally, the experimental group showed significant improvements on four of the five measures of syntactic complexity: MLT (t = 3.27, p = 0.002), C/T (t = 2.64, p = 0.011), CN/T (t = 3.01, p = 0.004), and MLC (t = 2.49, p = 0.016). Interviews with 12 participants revealed that AI feedback helped create a sense of linguistic safety and encouraged experimentation with more complex syntactic structures. These results suggest that AI-based writing assistants are effective in reducing anxiety and increasing syntactic complexity in second language writing.